The Perception of Japanese Cars by Market: Saudi Arabia and The United States and The Value Versus Price Proposition - Al Fayad, Fadye Saud (Archives of Business Research, 2019)
This study has worked to explore the characteristics of the Saudi Arabia new car market in comparison to certain aspects of the United States new car market. Specifically, this study sought to identify the unique perspectives that Saudi new car consumers have towards Japanese produced new cars compared to those of US new car consumers towards Japanese produced vehicles. Furthermore, the added element of identifying whether one market privileged value above price or price above value as a rationale in making a purchase decision was also examined. A quantitative methodology was utilized in approaching this research problem. The specific quantitative method selected was descriptive statistics because of its ability to isolate unique attributes in the data and to support conclusions about those attributes by quantifying consumer opinion in one respect or another. This study found that Saudi new car consumers in fact do have a positive perception of Asian and specifically Japanese produced cars. This assertion is supported both through the data and the fact that a Japanese car is currently the top selling new car sold in the Kingdom. Additionally, the data also finds that Saudi new car consumers tend to privilege the consideration of overall value as defined by efficiency, quality and price as a rationale to arrive at a purchase decision. Likewise, this study finds that the US new car consumer, while operating in a much different new car marketplace, tends to privilege price rather than value in the arrival at a purchase decision. Finally, this study also notes that the recent approval of women being able to drive in the Kingdom is a manifestation of the success of the Crown Prince’s Vision 2030 program. This development is indicative of the way in which the Vision 2030 objectives are remaking the Saudi economy, evidenced by the new car market, into a rich consumer-driven ecosystem capable of establishing the Kingdom as an international economic benchmark.